CONSIDERACIONES SOBRE LA MORFOLOGIA CRANEODENTARIA DE RUSCONIODON MIGNONEI BONAPARTE (CYNODONTIA, TRAVERSODONTIDAE): DIAGNOSIS, AFINIDADES Y VARIACIONES ONTOGENÉTICAS (Ameghiniana, 2013)
On the base of the study of recently collected specimens, the diagnosis of Rusconiodon mignonei Bonaparte (Cynodontia, Traversodontidae) is enlarged. Among the diagnostic features, the canine hypertrophy and the upper-labial perforation of the paracanine fossae are prominent and it is interpreted that the canine-fossa complex would have worked as an occlusion-guide—as well as in Andescynodon mendozensis Bonaparte (Cynodontia, Traversodontidae)—during the lower jaw closure. Both skull and teeth morphology basically correspond to those of A. mendozensis. Two ontogenetic stages among the analyzed specimens (preadult and adult) are recognized. An hypothesis related to the postacanine teeth replacement is proposed.